Degradação fotoquímica de hidrocarbonetos da gasolina em efluentes aquosos - Silva, Douglas do Nascimento (2002)
Photo-oxidation processes of toxic organic compounds have been widely studied. This work seeks the application of the photo-Fenton process for the degradation of hydrocarbons in water. The gasoline found in the refinery, without additives and alcohol, was used as the model pollutant. The effects of the concentration of the following substances have been properly evaluated: hydrogen peroxide (100-200 mM), iron ions (0.5-1 mM) and sodium chloride (200 2000 ppm). The experiments were accomplished in reactor with UV lamp and in a falling film solar reactor. The photo-oxidation process was monitored by measurements of the absorption spectra, total organic carbon (TOC) and chemical oxygen demand (COD). Experimental results demonstrated that the photo-Fenton process is feasible for the treatment of wastewaters containing aliphatic hydrocarbons, inclusive in the presence of salts. These conditions are similar to the water produced by the petroleum fields, generated in the extraction and production of petroleum. A neural network model of process correlated well the observed data for the photooxidation process of hydrocarbons